FEATURES OF ADMINISTRATIVE AND LEGAL REGULATION OF INFORMATION SECURITY IN APPLICATION OF INFORMATION TECHNOLOGIES AND AUTOMATED SYSTEMS IN THE CUSTOMS SECTOR IN THE CONTEXT OF THE IMPLEMENTATION OF THE «ONE WINDOW» MECHANISM - Салаєв, Тургут Гаджи огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to highlight the peculiarities of administrative and legal regulation of information security in the application of information technologies and automated systems in the customs sphere in the context of the introduction of the «one window» mechanism. Methods of research: in the work used general scientific and special methods. Results: the article considers the peculiarities of the activities of the fiscal authorities of Ukraine in the customs sphere, related to the collection, distribution, exchange, use of information, and therefore the relevance of improving information and telecommunication automated systems serving the above activities is justified. The novelty of the customs legislation of Ukraine, the «Single Window for International Trade» mechanism, was further investigated. In the system analysis with the information legislation, it is assigned to our main short stories in context of information protection. It is approved to the power of the information security service in the social sphere with the use of information technologies and automation systems in the context of the «single virtual» mechanism. Discussion: the issue of improving the administrative and legal framework of information security, developing a conceptual and systematic approach to the protection of information used, created and processed by revenue and customs authorities in the customs field.